Unleash the Potential of Mystery, Ghost & Paranormal Tourism through the lens of locals in Kuldhara, Rajasthan, India: A qualitative study - Sharma , Reena; SINGH, KULDEEP; Bagri, S.C. (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2023)
Mystery tourism is a novel topic related to travelling to events or destinations based on some stories, myths, beliefs of the host community or tourists. This also includes the myths and curiosity of locals and travelers about some known and unknown incidents or places. This paper aims to find out the experiences and perceptions of locals regarding mystery tourism in Kuldhara, Rajasthan. Ghost tours, paranormal investigations, and haunted stories have attracted many tourists to Kuldhara. In-depth interviews with 25 residents of Kuldhara, Rajasthan, reveal that residents have positive beliefs and ideologies regarding ghosts and paranormal activities. The study took in year (March 2022 to Feb 2023). The researchers identified purposive sampling and snow balling which has been used in previous studies too. This study is qualitative, and researchers employed thematic analysis techniques manually. Five major themes emerged from mystery tourism in Kuldhara, i.e., Myth & Tales, Perception of locals, Role of Government and Private bodies, Impact of mystery tourism and economic benefits. The study reveals that most locals face mysterious incidents and believe in ghosts and paranormal activities. This study generates curiosity among the readers and researchers to understand and explore the concepts of mystery tourism in a better way. Implications for developing mystery tourism attractions and support for resident well-being are offered.